Decision Making With Fuzzy Parameters When Modeling Preferences In Biotechnological Systems (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
The modeling of preferences in biotechnological systems when making decisions with fuzzy parameters was carried out. In this case, information about the object with the help of the decision maker is described in the form of a membership function that takes its values on a set of non-negative numbers. Three groups of preference relation models are considered, such as: clear preference relations, fuzzy preference relations, linguistic preference relations.